Inclusion of Indigenous Knowledge System (IKS) – A Precondition for Sustainable Development and an Integral Part of Environmental Studies - Carm, Ellen (Journal of Education and Research, 2014)
UNESCO (2005) launched the Decade of Education for Sustainable Development, 2005-2014, and as we now proceed into the final year of that decade there is a time for asking whose development? That question heavily relies upon what type of education, which again leads to aspects concerning epistemological lenses. I am using my experiences and research from two totally different assignments; an evaluation of a post-literacy and skills program in rural Laos, and the other aimed at developing and implementing a localized approach to HIV/AIDS education in Zambia. The outcomes from the two interventions revealed that in order to initiate and sustain change and development, it was crucial to ensure the inclusion and merger of multiple knowledge systems, science and traditional knowledge. That requires a focus on how. In other words, the processes we put in place to ensure the recognition and merger of different epistemologies are crucial to ensure sustained local development. The paper briefly discusses key concepts related to multiple knowledge systems, education for sustainable development, and different conceptualization of learning and teaching methods, and explores how environmental education can contribute to sustainable development. The last section illustrates how expansive learning can be applied as a method and a tool to analyze the processes at stake, and outcomes of participatory and inclusive interventions. The paper elaborates on the methodology and shows how a multi-voiced approach can bridge the gap between different epistemologies, e.g. Indigenous Knowledge and Western Knowledge, create space for interaction and negotiations among a diverse group of stakeholders and actors to reach to the local innovations and development activities. DOI: http://dx.doi.org/10.3126/jer.v4i1.10726 Journal of Education and Research, March 2014, Vol. 4, No. 1, pp. 58-76